Spies: The Secret Agents Who Changed the Course of History - Ernest Volkman; VOLKMAN (Ernest) (New York John Wiley and Sons Inc, 1994)
"Intriguing." $1 (BBooklist "Ernest Volkman brings his subjects into full life in their world of espionage. Spies is a substantial addition to the already rich collection of titles under his name." $1 (BRay S. Cline, President National Intelligence Study Center "A consistently absorbing and informative introduction to key players in the espionage game." $1 (BKirkus Reviews Acclaimed author Ernest Volkman strips away the myths and Hollywood hype to reveal the human drama behind "the world$1 (Bs second oldest profession"$1 (Bespionage. Spies is the startling true story of the men and women whose daring feats of subterfuge have, for better or worse, irrevocably altered the course of history.s
Keywords: Military intelligence--History--20th century; Espionage--History--20th century